Effects of noises on curve fitting to the I–V characteristics of retarding filed analyzers. Issue 1 (2nd January 2020) - Sun, C. Y.; Li, Y. L.; Voldiner, I.; Pan, L.; Yan, N.; Zhang, H.; Xiao, C.
Abstract : Retarding filed analyzers (RFAs) measure the ion velocity distribution in edge plasmas, leading to an estimate of the ion temperature and space potential through curve fitting. This paper describes the bi-directional RFA detector installed on the Experimental Advanced Superconducting Tokamak for edge plasma parameter measurements. The paper also describes a technique to compensate for a known induced noise using a dummy signal line and a method to reconstruct the I–V curve from the scanning voltage signal and the resultant ion current waveform. Fitting to experimental data and numerical simulations show that the I–V curve reconstruction method serves for both smoothing and induction noise compensation purposes.